Ethnomathematics exploration of the Malay traditional house Indera Perkasa Penyengat Island, Riau Islands - Alwahab, Putri Annisa; Cancerlia, Cindy; Hani, Zikra; Lestari, Putri Indah; Husna, Asmaul (Universitas Riau Kepulauan, 2023)
Mathematics learning is often considered a difficult and boring lesson so that many students do not understand the material provided by the teacher, so teachers are required to be more innovative, creative and varied in learning mathematics. One aspect that can be developed to make this learning more varied is by linking mathematics and culture which is called ethnomathematics. Indonesia is an archipelago that has a lot of cultural diversity. One of the cultural varieties originating from the Riau Islands is the Malay Archipelago Ornament. Nusantara Malay ornaments contain philosophy and life values that are very closely related to the Malay community of Riau Islands. This research was conducted to identify ethnomathematics contained in the Riau Islands Malay ornaments in the concept of mathematics, namely geometric transformation. The location where the research was conducted was the Indera Perkasa Malay Customary Hall located on Penyengat Island, Tanjung Pinang. The approach used is ethnography with qualitative research type. Data were obtained using observation and documentation techniques. The data analysis technique used is qualitative data analysis technique which consists of three steps, namely data reduction, data display, and conclusion drawing. The results showed that in the Malay ornament of Riau Islands there is a concept of geometry transformation, namely translation and reflection.